WaterS: A Sigfox‐compliant prototype for water monitoring. Issue 1 (4th October 2018) - Di Gennaro, Pietro; Lofú, Domenico; Vitanio, Daniele; Tedeschi, Pietro; Boccadoro, Pietro
Abstract : The Internet of Things (IoT) represents the enabling paradigm of a huge number of smart applications, spanning from short‐range communications to Low‐Power Wide‐Area Network (LPWAN). Among them, environmental monitoring becomes more and more challenging as the area of interest is difficult to reach. The present contribution proposes WaterS, an open‐source project that relies on low‐cost and rapid‐prototyping technologies. It tackles the main challenges of remote water quality monitoring systems taking advantage of the Sigfox protocol stack. The realized experimental setup is able to gather geo‐referenced water quality measurements. Finally, it successfully addresses self‐sufficiency thanks to solar energy harvesting.